Student Career Decision Making: Self-Efficacy and Future Orientation - Alif Muarifah; Titah Nurliyana (IJIP : Indonesian Journal of Islamic Psychology, 2022)
This study aims to empirically examine the effect of career decision-making on self-efficacy and future orientation. This research method uses a quantitative using cluster random sampling technique. The number of subjects used amounted to 177 SMK students. The data analysis technique used multiple linear regression. The results of hypothesis testing together obtained an R-value of 0.693 with a significance value of 0.000 (p < 0.01). It is concluded that the hypothesis is accepted, that is, there is a significant influence between self-efficacy and future orientation on career decision-making. This means that a higher level of self-efficacy and future orientation strongly influence career decision-making. The first minor hypothesis test obtained a t-value of 4.834 with a significance level of 0.000 (p <0.01). It is concluded that the hypothesis is accepted; self-efficacy has a very significant positive effect on career decision-making. The results of the second minor analysis obtained a t-value of 2.832 with a significance level of 0.005 (p <0.05). It is concluded that the hypothesis is accepted; future orientation has a very significant positive effect on career decision-making.